Screening of Mutants in Black Gram (Vigna mungo (L.) Hepper) With Effect of DES and COH in M2 Generation - S. Velu, D. Arulbalachandran, L. Mullainathan (Journal of Phytology, 2009)
Cultivars developed using induced mutants may carry improvements in a wide variety of characteristics. Induced mutant cultivars also have proved to be outstanding parents for further cultivar development. The efficiency of induced mutations in increasing genetic variability has been demonstrated in several crops and a number of varieties have been evolved. In the present investigation, chlorophyll mutants chlorino, albino, xantha, variegata and viridis and morphological mutants such as, dwarf, tall, onostem, tiny leaves, hairy leaves, male sterility, brown seed, early maturity, long pod, bottom branching, top branching, trailing, spreading, and bushy type in M2 generation from both Diethyl sulphate (DES) and Colchicine (COH) treated populations. Mutants and mutant derivatives when used in cross breeding were found to be more productive in the development of improved varieties of black gram. Moreover, induced mutations have recently become the subject of molecular investigations leading to descriptions of the structure and function of related genes. Mutated genes have therefore; become valuable material to plant breeders and molecular biologists for understanding not only the function but also in isolating and shuffling the genes between varieties.